(untitled) (Research, Society and Development, 2024)
The use of sand as a substrate in nutritional studies is frequent, but there is no formal protocol for cleaning and purifying this substrate for various agronomic studies, including those related to plant nutrition. The study aimed to evaluate the changes in chemical attributes resulting from the cleaning and purification of common construction sand. The experimental study, of a quantitative nature, was carried out under greenhouse and laboratory conditions. An experiment was carried out whose treatments were levels of hydrochloric acid (HCl) concentration, immersion times in the acid solution, and purification in an autoclave. It was found that sterilization in an autoclave significantly decreased the pH of the sand and increased the phosphorus content. From a day of rest with HCl, the decrease in the pH of the sand was significant. On the other hand, the phosphorus content increased linearly with the immersion time in HCl. The use of HCl completely eliminated the levels of potassium, calcium, magnesium, and copper, and significantly decreased the contents of iron and manganese (above 70%) and zinc (above 80%). To exhaust or significantly decrease the levels of nutrients present in the sand, one should use 3% HCl, without rest, for phosphorus and one day of incubation for potassium, calcium, magnesium, and copper, iron, manganese, and zinc.